2021
DOI: 10.7759/cureus.16988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Integrated Plastic Surgery Residency Match During the Novel Coronavirus Pandemic

Abstract: The COVID-19 pandemic had significant impacts on medical education and on the 2021 Match. Visiting student rotations at locations other than students' home institutions were cancelled and residency interviews were hosted virtually. This study evaluated the impact that COVID-19 had on the 2021 Match including residency programs matching applicants from within their own institution as well as from within the same region. The sex of matched applicants in the Match cycles was analyzed as well. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 11 publications
(19 reference statements)
3
23
0
Order By: Relevance
“…Similarly, there was an 8.4% increase in home program matches observed when looking at integrated plastic surgery residency, another competitive surgical subspecialty. 8 These trends are consistent with what many have hypothesized with the changes that occurred due to COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, there was an 8.4% increase in home program matches observed when looking at integrated plastic surgery residency, another competitive surgical subspecialty. 8 These trends are consistent with what many have hypothesized with the changes that occurred due to COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…Two recent studies also identified an increase in applicants matching at their respective home programs [ 6 , 12 ]. Additionally, this was also similar to what was seen in the integrated plastic surgery match, another competitive surgical specialty, in 2021 where there was a 9% increase in HP matches [ 13 ]. Similar trends are also seen outside the surgical residency programs, with a 9.1% increase in HP matches seen in dermatology in 2021 [ 14 ].…”
Section: Discussionsupporting
confidence: 72%
“…Numerous studies evaluating 2021 match data showed a significant increase in applicants matching at their home institutions compared with previous years. [8][9][10][11][12][13][14][15] The link between these changes and the COVID-19 pandemic has been described in detail. Among students interested in plastic surgery, COVID-19 not only affected the residency application process but also negatively impacted these students' confidence in their medical education.…”
Section: Introductionmentioning
confidence: 99%